Design, Development and Fabrication of A Single Row Manual Vegetable Transplanter - Kumar, Vinay; Dixit, Jagvir (Indian Journal of Hill Farming, 2018)
Present study was carried out during the year 2015-16 to design, develop and evaluate the single row manual vegetable transplanter on three different types of vegetable crops i.e.brinjal, chilli and tomato at two different sites and compare it with traditional method of transplanting. The manual single row vegetable transplanter consists of different component like hopper, handle, seedling delivery tube, jaw opening lever and jaw mouth. The implement penetrates into the soil by applying little force while holding with handle, seedling is dropped into seedling delivery tube then the jaw is opened with lever. The work demonstrates the application of engineering techniques to reduce the labour efforts and time required for transplanting. The results obtained from the trial tests concluded that transplanter functioned properly as there is no miss planting, also the rate of tilted planting is negligible. The mean effective field capacity was 52.36 percent higher over traditional method of transplanting. Significantly lower labour was required with developed prototype over traditional method with an average saving of 52.83 percent of time and labour.